Arene ruthenium(II) complexes with 2-acetamidothiazole derived ligands: Synthesis, structural studies, antifouling and antibacterial properties. (4th November 2015) - Singh, Keisham S.; Devi, Prabha; Sawant, Sneha G.; Kaminsky, Werner
Graphical abstract: Four related arene ruthenium(II) complexes containing 2-acetamidothizole derived ligands have been prepared and characterized spectroscopically. Antifouling and antibacterial properties against marine fouling bacteria and clinical isolates were evaluated. The molecular structure of a representative compound has been established by single crystal X-ray analysis. Abstract: Four related arene ruthenium(II) complexes with antifouling properties of the general formula [(η 6 -arene)Ru(L)Cl2 ] have been prepared by the reaction of [(η 6 -arene)RuCl2 ]2 with 2-acetamidothiazole derived ligands at room temperature (η 6 -arene = p -cymene, C6 Me6 ; L = 2-acetamidothiazole or 5-chloro-2-acetamidothiazole) and were characterized by FTIR, 1 H, 13 C NMR and mass spectral analysis. The antifouling properties of these ruthenium(II) complexes have been investigated against marine fouling bacteria and the antibacterial properties against clinical pathogens. The complexes showed moderate to good antifouling as well as antibacterial activities. The molecular structure of a representative compound has been established by single crystal X-ray diffraction.